Rwanda : Technical Assistance Report-Government Finance Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission to assist authorities in Rwanda in aligning the compilation and dissemination of government finance statistics (GFS) in accordance with the Government Finance Statistics Manual 2014. It was recommended that the Ministry of Finance (MINECOFIN) should officially assign GFS compilation duties to a specific subset of its staff. The mission believes that it is important for the MINECOFIN to make a 'permanent' assignment of GFS compilation and dissemination duties so that the work can evolve systematically. In the mission's view, the Macroeconomic Policy Unit appears to be well placed to perform this task. However, the unit should be allocated appropriate resources to take on the responsibility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; Data; Government; ISCR; Work Program; Rwanda